Pengaruh Motivasi dan Kompensasi terhadap Kinerja Karyawan Di PT Almanova Jaya Persada - Noviani, Nurul; Hastasari, Ratih; Setiawan, Wawan (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
In facing increasingly intense business competition, companies are required to have high-quality and competitive human resources. Employee performance is a key factor in achieving organizational goals, therefore an effective human resource management strategy is essential, including enhancing motivation and providing adequate compensation. Based on this, the purpose of this study is to determine the effect of motivation and compensation on employee performance at PT Almanova Jaya Persada. The population in this study consists of all employees of PT Almanova Jaya Persada, totaling 82 individuals. Since the number is relatively small, the entire population was used as the sample using a saturated sampling technique. This research employs a quantitative approach. Data were collected through questionnaires and analyzed using validity and reliability tests, classical assumption tests (normality, heteroscedasticity, multicollinearity), multiple linear regression analysis, t-test, F-test, and coefficient of determination test, with the help of IBM SPSS version 27 software. The results of the study show that motivation has a positive and significant effect on employee performance with a t-value of 8.883, and compensation also has a positive and significant effect with a t-value of 2.046. Simultaneously, motivation and compensation have a significant effect on employee performance with an F-value of 85.334. The resulting regression equation is: Y = 1.022 + 0.807X1 + 0.180X2